31P Nuclear Magnetic Resonance of Charge-Density-Wave Transition in a Single Crystal of RuP*Supported by the National Natural Science Foundation of China under Grant No 11025422, the National Basic Research Program of China under Grant Nos 2011CB921700 and 2015CB921300, and the Strategic Priority Research Program of the Chinese Academy of Sciences under Grant No XDB07020200. (July 2015) - Fan 范, Guo-Zhi 国志; Chen 陈, Rong-Yan 荣艳; Wang 王, Nan-Lin 楠林; Luo 雒, Jian-Lin 建林
Abstract : We perform 31 P nuclear magnetic resonance (NMR) measurements on a single crystal of RuP. The anomalies in resistivity at about TA = 270 K and TB = 330 K indicate that two phase transitions occur. The line shape of 31 P NMR spectra in different temperature ranges is attributed to the charge density distribution. The Knight shift and spin-lattice relaxation rate 1/T1 T are measured from 10 K to 300 K. At about TA = 270 K, they both decrease abruptly with the temperature reduction, which reveals the gap-opening behavior. Well below TA, they act like the case of normal metal. Charge-density-wave phase transition is proposed to interpret the transition occurring at about TA .